Evaluating the Optical Properties of the Schmidt Cassegrain Spider Obscuration Telescope Using Zemax Program - b. hasan, alaa (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2022)
Schmidt Cassegrain spider obscuration telescope (SCT) is one of the types of observations operating with a concave mirror. It combines several lenses and mirrors working together as an optical system. The light rays fall into the tube from the main mirror and gather on another smaller mirror called a secondary mirror. Unlike the formation of Newton's telescope, no light is made from the secondary mirror out the side of the tube but is directed to the middle of the main mirror. There is an opening in the middle of the main mirror so the light beam can go out and direct the vision lens system. The secondary mirror is located in the middle of a glass slice and is installed by thin carriers. The function of this board is to correct the portrait of the significant spherical mirror and reduce this coma aberration in the system to the lowest possible score.In this research, the efficiency of design performance was studied due to image analysis tools provided by the Zemax program. The results showe the image quality when using a variable field of view with a limit (0o- 0.5o) and for a variable focal depth as needed.